2001
DOI: 10.1034/j.1600-0714.2001.300911.x
|View full text |Cite
|
Sign up to set email alerts
|

PTCH gene altered in dentigerous cysts

Abstract: Motivated by the evidence that odontogenic keratocysts are associated with genetic alterations, we examined the possibility that development of other odontogenic cysts can be attributed to gene malfunctioning, in particular to the PTCH gene. Cyst epithelium was examined for polymorphism on chromosome 9q22.3, the region that contains the PTCH gene. Loss of heterozygosity (LOH) for the D9S287 marker and/or D9S180 marker was observed in about 50% of dentigerous cysts, whereas radicular cysts gave no indication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 15 publications
1
28
0
6
Order By: Relevance
“…Surprisingly, some OOC cases presented the same alteration. LOH of the PTCH gene was previously reported in dentigerous cyst (24, 27), and recently, mutations of PTCH gene were also reported in calcifying epithelial odontogenic tumor (28). Additionally, a previous study identifies similar expression of the SHH pathway proteins SHH, PTCH, SMO, and GLI in KOTs, OOCs, dentigerous cysts, radicular cysts, and ameloblastoma (12).…”
Section: Discussionmentioning
confidence: 94%
“…Surprisingly, some OOC cases presented the same alteration. LOH of the PTCH gene was previously reported in dentigerous cyst (24, 27), and recently, mutations of PTCH gene were also reported in calcifying epithelial odontogenic tumor (28). Additionally, a previous study identifies similar expression of the SHH pathway proteins SHH, PTCH, SMO, and GLI in KOTs, OOCs, dentigerous cysts, radicular cysts, and ameloblastoma (12).…”
Section: Discussionmentioning
confidence: 94%
“…Some research has shown that DC can also be caused by the functional loss of PTCH. Some researchers thought DC might be a symptom of NBCCS 10,12 . In this family, all the patients carried the same mutation of PTCH.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Genetic mutations have also been proposed as a possible cause in the development of odontogenic cysts like odontogenic keratocyst (OKC)[2] and dentigerous cyst. [3] Studies investigating the cell kinetics of epithelial linings of odontogenic cysts indicate that the lining of OKC may have some intrinsic growth potential which is not present in other cysts[45] and thus OKC is now regarded as a benign cystic neoplasm rather than a cyst. [67]…”
Section: Introductionmentioning
confidence: 99%